Exploring the Ecological Preferences and Essential Oil Variability in Wild-Growing Populations of the Endangered Local Greek Endemic Thymus holosericeus (Lamiaceae) - Olga S. Tsiftsoglou; Rafaela Stagiopoulou; Nikos Krigas; Diamanto Lazari (Plants, 2023)
Thymus holosericeus Čelak. (Lamiaceae) is a taxonomically isolated and endangered local endemic thyme species which is geographically isolated in four Ionian Islands (West Greece). The present study investigated the essential oil (EO) composition, the ecological preferences, and their correlations in three T. holosericeus wild-growing populations from Zakynthos (ΤH-Z), Cephalonia (ΤH-C) and Lefkada (ΤH-L). The variations in essential oil yield and the composition of T. holosericeus populations were evaluated using hydrodistillation, GC/MS, TLC and NMR analysis. The climatic conditions of each sample were organized and analyzed in RStudio with the raster package and in SPSS with Pearson’s Canonical Correlation Analysis (CCA), respectively. The aerial parts of the plants varied in EO yields from 1.92 to 2.28% w/v. The analysis of EO constituents revealed noteworthy qualitative and quantitative inter-population variation. The composition of EOs revealed the presence of linalool (82.77%) and borneol (5.95%) as major compounds in ΤH-Z, while carvacrol (35.34%), geraniol (23.98%), linalool (14.37%), borneol (5.66%), thymol (4.27%) and p-cymene (4.08%) were the main compounds in ΤH-C and linalool (40.37%), geraniol (39.42%) and borneol (5.20%) were dominant components in ΤH-L. The results of the gas chromatography procedure have also been confirmed by 1H and 13C-NMR and TLC analysis. The ecological profile showed an average annual precipitation of 942 ± 18.33 mm and the temperature limits in which T. holosericeus seems to adapt to are 6.80± 1.08 °C 27.70 ± 0.70 °C. Regarding the examined samples, TH-C was adapted to the driest summer and coldest winter conditions, TH-Z was adapted to the lowest annual precipitation with the most complex climatic conditions, and TH-L was adapted to the highest summer temperatures with the lowest precipitation in the wettest period of the year. For each sampled population, the CCA identified the association of the samples’ EOs composition with the prevailing local environmental conditions.